Modeling of laminar filmwise condensation of methane with nitrogen on an isothermal vertical plate. (June 2019) - Zhang, Lili; Zhang, Guanmin; Tian, Maocheng; Zhang, Jingzhi; Zhang, Yi
Abstract: Liquefied natural gas (LNG) is one of the key technologies in the development and utilization of natural gas. To clarify the condensation characteristics at the last stage of natural gas liquification, saturated methane mixed with nitrogen was chosen as the study object. A numerical model was proposed to predict the filmwise condensation characteristics of ultralow temperature (−162 °C) vapor with non-condensable gas on an isothermal vertical plate. The gas-liquid interface was captured using the Volume of Fluid (VOF) method. A user defined function (UDF), which was written using a cell iteration method and based on the mass conservation on the gas-liquid interface, was applied to deal with the mass and energy source term of the condensing process. The subcooled temperature (temperature difference between wall and saturated gas) and the molar content of non-condensable gas were 2-20 K and 2–13%, respectively. The numerical results show that the heat and mass transfer occur mainly near the cool wall in millimeter level, with the change of temperature, viscosity, phase and mole fraction. A small amount of non-condensable gas can reduce heat transfer coefficients significantly. When the mole fraction of non-condensable gas is 2%, the heat transfer coefficient is reduced by about 59%. And the heat and mass transfer resistance are mainly in the vapor-gas boundary layer rather than in the liquid film.